Enhancing Employee Potential: Using Talent Mapping to Drive Talent Mobility at PT Mifa Bersaudara - Firmansah, Hadi; Hadi, Fajmal (Publikasi Indonesia, 2025)
In coal mining industries where operational complexity and strategic growth are increasing, the challenge of identifying and developing internal talent is critical. PT Mifa Bersaudara, a coal mining company in Aceh, Indonesia, faces the need to optimize human resource potential to ensure leadership continuity and internal talent mobility. This study aims to implement a systematic talent mapping framework by combining the HAV Matrix and 9-Box Grid to assess employee performance and potential. Employing a quantitative descriptive approach with secondary data from 140 employees, the research uses KPIs, compliance indicators, leadership traits, certifications, and external assessments to evaluate talent readiness. Employees were categorized using a weighted scoring method and visualized in the 9-box grid to support strategic HR decisions. The results revealed that 68 employees fall into the “Developing Top Performers” category and 33 into the “Effective Performers” group, indicating a strong pipeline for future leadership roles. The study concludes that structured talent mapping enhances workforce alignment, boosts employee engagement, and supports sustainable succession planning. It also serves as a reference for other organizations aiming to institutionalize data-driven human resource development.